Fabricating hydrophilic fatty acid-protein particles to encapsulate fucoxanthin: Fatty acid screening, structural characterization, and thermal stability analysis. (15th July 2022) - Li, Donghui; Liu, Yunjun; Ma, Yu; Liu, Yixiang; Wang, Shengnan; Guo, Zixin; Li, Jie; Wang, Yanbo; Tan, Bin; Wei, Ying
Graphical abstract: Highlights: Dietary fatty acids (FAs) showed different regulatory effects on the intestinal absorption of fucoxanthin (FUCO). Myristic, palmitic, stearic, oleic, linoleic, and docosahexaenoic acid obviously promoted FUCO absorption. The encapsulation efficiency of FAs-bovine serum albumin (BSA) particles to FUCO reached>98%. The FUCO-loading particles exhibited a "core-shell" structure. The FAs-BSA particles improved the thermal stability of FUCO by 2.16–4.06 times. Abstract: Biomacromolecules are used to encapsulate carotenoids, but their poor absorption-enhancing ability restricts their application. This study integrated dietary fatty acids (FAs) into the protein-based encapsulation of fucoxanthin (FUCO) due to its positive role in carotenoid absorption. The results showed that of the 14 tested FAs, only myristic, palmitic, stearic, oleic, linoleic, and docosahexaenoic acid obviously promoted FUCO absorption. FAs were employed for FUCO encapsulation using bovine serum albumin (BSA) to fabricate FUCO-FA-BSA systems, with an encapsulation efficiency of > 98%, a particle size ranging from 113.1 nm to 193.5 nm, and a Zeta-potential between −32.8 mV and −38.3 mV. Electron microscopy and Fourier transform infrared spectroscopy revealed complete FUCO encapsulation, while the FUCO-loading particles exhibited a "core-shell" structure. The retention rate of the encapsulated FUCO increased 2.16–4.06 times when heated at 80.0 °C for 200 min. These results suggested that FA-BSA complexes might provide a promising strategy for embedding carotenoids.